Android Studio IDE quick reference : a pocket guide to Android Studio development - Hagos, Ted (Apress, 2019)
This concise reference book for Android Studio 3 presents the essential Android Studio functions in a well-organized format that can be used as a handy reference. It will quickly demonstrate the usage of the Android Studio IDE to build an Android mobile app step by step. You won't find any technical jargon, bloated samples, drawn out history lessons, or witty stories in this book. What you will find is a reference that is concise, to the point and highly accessible. The Android Studio IDE Quick Reference is packed with useful information and is a must-have for any mobile or Android app developer or programmer. What You Will Learn Discover the workflow basics in Android Studio 3 Make tasks efficient with keyboard shortcuts Carry out unit testing in Android Studio 3 Use time-saving techniques such as templates Master debugging basics Configure your project using Gradle Use the profiler to monitor app performance Who This Book Is For Those who already know how to build applications in Android using Java. This book will serve as a handy and quick reference on how to get things done in Android Studio 3.